1996
DOI: 10.3354/dao025225
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of the transmissible green turtle fibropapillomatosis agent to chloroform and ultracentrifugation conditions

Abstract: Transmission experiments were conducted to further characterize the filterable transmissible agent that causes GTFP, fibropapillomatosis of green turtles Chelonja mydas. Cell-free homogenates (unfiltered or 0.45 pm filtered), prepared from fibropapillomas of free-ranging green turtles (donors) and inoculated into 18 captive-reared recipients, induced tumors in recipients with an overall success rate of 83.3 % (range: 0 to 100 %). Chloroform treatment prior to inoculation destroyed tumorigenic activity of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
19
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 1 publication
5
19
0
1
Order By: Relevance
“…Sea turtles undergo an oceanic stage during the first few years of their lives, while as juveniles they recruit to coastal foraging habitats where they remain for several years. Mature individuals move periodically from neritic bays to nesting beaches and mating areas, Our results support the conclusion that horizontal transmission in neritic bays is the major route by which individuals become infected, which is further supported by the demonstration that infectious CFPHV particles are transmitted along with FP through skin lesions (Herbst et al, 1995(Herbst et al, , 1996.…”
Section: Discussion Host Life History Implications For the Phylogeogrsupporting
confidence: 74%
“…Sea turtles undergo an oceanic stage during the first few years of their lives, while as juveniles they recruit to coastal foraging habitats where they remain for several years. Mature individuals move periodically from neritic bays to nesting beaches and mating areas, Our results support the conclusion that horizontal transmission in neritic bays is the major route by which individuals become infected, which is further supported by the demonstration that infectious CFPHV particles are transmitted along with FP through skin lesions (Herbst et al, 1995(Herbst et al, , 1996.…”
Section: Discussion Host Life History Implications For the Phylogeogrsupporting
confidence: 74%
“…Transmission studies have demonstrated that the infectious FP agent is less than 0.45 m in size and can be inactivated by organic solvents and high-speed centrifugation, which is consistent with the theory of an enveloped virus as the causative agent (36,37). Using PCR, FPTHV DNA has been found in most examined fibropapillomas but not detected in the vast majority of healthy turtles (45,47,54).…”
supporting
confidence: 51%
“…In addition, the spatial distribution and association of specific closely related CFPHV variants found in turtles with FP with particular nearshore localities (such as the Indian River Lagoon) suggests that turtles become infected with CFPHV after they migrate as juveniles to these localities (10). The epizootic transmission cycle is perpetuated in areas with high FP prevalences, as tumors are a known source of transmissible virus (21,24). The high prevalence of CFPHV gH antibodies in the Trident Basin population suggests, however, that there may be alternate virus transmission cycles involving virus replication and shedding from tissues other than cutaneous tumors.…”
Section: Discussionmentioning
confidence: 99%
“…A series of green turtles that had been raised from eggs in captivity for use in transmission experiments provided a source of plasma samples with well-controlled exposure to CFPHV and limited exposure to other pathogens (21,24). Samples that were collected from these turtles prior to any experimental exposure to CFPHV (preinoculation samples and controls) were used as our population of "known negatives."…”
Section: Expression Of Recombinant Gh (Ul22) and Gl (Ul1)mentioning
confidence: 99%